Immune response and host-pathogen interactions. - Pollard, A; Goldblatt, D (2001)
For the most part, the relationship between the pathogen, Neisseria meningitidis, and humans is uneventful. Colonization of the human nasopharynx at various times during life is an almost universal experience but clinically overt disease is unusual except during epidemics. This overview considers the relationship between the meningococcus and humans, reviewing current immunological and molecular understanding of this interaction of relevance to development of immunogenic vaccines.